Molecular prevalence and genome analysis of domestic cat hepadnavirus in Malaysia - Anpuanandam, Khanmani (2021)
Domestic cat hepadnavirus (DCH, genus Orthohepadnavirus, family Hepadnaviridae) was first reported from whole blood samples of domestic cats in Sydney, Australia in 2018. Following that, DCH have been detected from various tissues including serum, formalin-fixed, paraffin embedded liver tissues, kidney, lung, heart, intestine, brain and lymph nodes. The pathogenesis of DCH is still unknown, but it was reported in cats with viraemia (6.5-12.4%), hepatocellular carcinoma (28%) and chronic hepatitis (43%). To date, there are no data regarding molecular prevalence of DCH among domestic cats in Malaysia. Moreover, detection of DCH in paired blood and liver samples of individual cats are not documented. In this study, the objectives are to determine the molecular prevalence of DCH from blood and liver tissues using conventional PCR method and evaluate the association of DCH with common feline viral diseases and hepatopathies. In addition, complete genome sequence (CGS) and phylogenetic analyses of Malaysian DCH compared to known DCH isolates and other hepadnaviruses were also included as in the objective. A cross-sectional study was done using 253 whole blood, 87 fresh liver tissues and 20 archived liver samples which includes domestic cats from animal shelters and patients of University Veterinary Hospital (UVH). The risk factors associated with DCH were analysed by using IBM SPSS 22 which included Chi-square and Fisher’s exact test method. Survey criteria included origin, sex, age, status of common feline viral diseases, serum biochemistry level and hepatic lesions of the cats. Phylogenetic tree using CGS was plotted by using maximum likelihood approach available in Molecular Evolutionary Genetics Analysis (MEGA7). Histological slides of liver tissues were evaluated based on World Small Animal Veterinary Association (WSAVA) standards and graded using modified Ishak score method. From whole blood samples, 12.3% (n = 32/253) were tested DCH-positive. Prevalence of DCH was significantly higher in pet cats (16.6%, n = 24/145) compared to shelter cats (6.5% (n = 7/108). Among the DCH positives, 62.5% (n = 20/32) were cats more than 2 years old. Liver samples showed higher DCH detection rate (14.9%, n = 13/87) compared to blood samples. Five out of these 13 cats tested positive for DCH in their paired liver and blood samples. Serum alanine transaminase (ALT) level was elevated (> 95 U/L) in 12 out of the 23 DCH-positive cats (52.2%, p = 0.012). Upon histopathology, 3 out of 4 liver tissue with lymphoid aggregates were also positive for DCH (p = 0.001). From CGS analysis Malaysian DCH strain, with a genome size of 3184 bp was obtained with lowest genetic variability to Thailand DCH strain. The phylogenetic analysis demonstrated that the Malaysian DCH strain clustered together into same branch with Australian strain showing that the Malaysian and Australian DCH strains have a common ancestor. The present study reports DCH as a common feline virus among domestic cats of Malaysia with risk factors associated with origin, and age of the cat. This study provides insights on a new variant of DCH detected and sequenced for the first time from fresh liver tissue sample. The impact of this virus on inducing liver-related diseases in felines warrants further investigation.